Straightforward Synthesis of Isoellipticine by Palladium‐Catalysed Coupling Reactions. Issue 2 (9th January 2018) - Naciuk, Fabrício F.; Castro, Joaquim A. M.; Serikava, Bruno K.; Miranda, Paulo C. M. L.
Abstract: Our novel synthetic route to isoellipticine featured palladium‐catalyzed intramolecular reactions for the construction of the B ring of the pyridocarbazole nucleus. The adequate palladium‐catalyzed reaction depended upon the oxidation conditions that were applied in order to prepare the immediate synthetic precursor. When CAN was used to make the quinone intermediate, an oxidative cyclization through a double C−H bond activation was applied. Conversely, when the oxidation condition involved TCCA as oxidant, a direct C−H arylation was employed. Both approaches showed similar efficiencies in order to construct the pyridocarbazole nucleus. Isoellipticine was prepared in only 5 steps with a 21%–23% overall yield. Abstract : We describe the synthesis of the isoellipticine using two different palladium‐catalyzed reactions in five steps and 21–23% global yield. A tuned oxidation reaction capable of generating two different quinones was used to prepare the substrates for the oxidative cyclization through double C−H bond activation and for the direct C−H arylation.